A novel Aβ epitope vaccine based on bacterium-like particle against Alzheimer's disease. (September 2018) - Fu, Lu; Guo, Yongqing; Sun, Yao; Dong, Yue; Wu, Jiaxin; Yu, Bin; Zhang, Haihong; Yu, Xianghui; Wu, Hui; Kong, Wei
Highlights: Alzheimer's disease vaccine using the Aβ1–6 epitope is safe and effective. The BLP-based AD vaccine induced antibodies against Aβ42 without T-cell activation. A suitable epitope copy number improved the immunogenicity of the vaccine. Antibodies effectively blocked toxicity of Aβ42 oligomer at the cellular level. Abstract: Amyloid-beta (Aβ) plaque accumulation in the brain is one of the hallmarks of Alzheimer's disease (AD). Immunotherapy against Aβ was considered a potential strategy for reducing the Aβ load in the brain. However, none of the Aβ immunotherapies have produced clinically meaningful results to date, due to poor safety or lack of efficacy. Thus, we aimed to design a safe and effective vaccine against AD. In this study, we used bacterium-like particles (BLPs) as carriers and different copy numbers of the Aβ 1-6 peptide as epitopes to design four Aβ active immunization vaccines. The epitopes containing different copy numbers of the Aβ 1-6 peptide were specifically loaded on the surface of BLPs via fusion with a peptidoglycan anchoring domain. These four BLP-based Aβ vaccines successfully induced high levels of Aβ42-specific antibodies in mice. However, none of the vaccines induced a T-cell-mediated immune response. Importantly, the antibodies induced by these four vaccines were effective in blocking Aβ42 oligomer toxicity at the cellular level. Among the four vaccines, 6copy-Aβ 1-6 -PA-BLP was the most effective in inducing Aβ-specific antibodies, indicating that a suitable epitope copy number is critical for high immunogenicity of the BLP-based vaccine. Furthermore, high levels of serum Aβ-specific antibodies could still be detected 3 months after the final administration of 6copy-Aβ 1-6 -PA-BLP. Thus, 6copy-Aβ 1-6 -PA-BLP may be a potential therapeutic treatment for AD.